2020
DOI: 10.1177/0018720820948303
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Increased Activities of the Forearm Muscles Due to Anti-Vibration Gloves: Construct Validity of a Refined Methodology

Abstract: Objective The primary aim was to test the construct validity of a surface electromyography (EMG) measurement protocol, indirectly assessing the effects of anti-vibration (AV) gloves on activities of the forearm muscles. Background AV gloves impose a relatively higher grip demand and thus a higher risk for musculoskeletal disorders. Consequently, activities of the forearm muscles should be considered when assessing AV glove performance. Method Effects of AV gloves on activities of the forearm muscles (ECR: exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The thinnest glove (glove 2) showed the lowest grip strength decline (6.8%). The reason for this may be that our glove thickness was in a narrower range (1.03 mm~2.17 mm) than that in [49] (1.2 mm~8.2 mm). This may also imply a decline of grip strength due to wearing gloves not only depending on glove thickness but also the stiffness of the gloves.…”
Section: Grip Strengthmentioning
confidence: 88%
See 1 more Smart Citation
“…The thinnest glove (glove 2) showed the lowest grip strength decline (6.8%). The reason for this may be that our glove thickness was in a narrower range (1.03 mm~2.17 mm) than that in [49] (1.2 mm~8.2 mm). This may also imply a decline of grip strength due to wearing gloves not only depending on glove thickness but also the stiffness of the gloves.…”
Section: Grip Strengthmentioning
confidence: 88%
“…The cut resistance gloves (glove 3) showed the highest decline than the other gloves, and the knitted gloves with NBR coating showed the lowest decline. Based upon EMG assessments of forearm muscles, a literature [49] has found that declination of grip strength is linearly related to the thickness of the gloves. This was partially consistent with our findings.…”
Section: Grip Strengthmentioning
confidence: 99%
“…A review of studies employing these sensors is summarized in Table 1, where each is identified by the lead author alone. EMG sensors measure minute electrical signals (muscle action potentials) produced during muscle contractions on the body's surface, which have found increasing applications across various fields, such as enhancing speech recognition [31], force estimation [32], and refining disease identification accuracy based on specific features [33]. The introduction of EMG sensors has significantly aided [25], (b) force sensor [26], and (c) displacement sensor [27].…”
Section: Human Signal-monitoring Sensorsmentioning
confidence: 99%
“…An alternative way that indirectly assesses grip force is through the activities of forearm muscles using surface electromyography (EMG) (Dianat et al, 2010;Larivière et al, 2004). The four main forearm muscles, including flexor carpi radialis (FCR), flexor digitorum superficialis, extensor carpi radials (ECR), and extensor digitorum, that closely activate when gripping a handle were used in several studies to assess the influence of various grip strength on the development upper limb fatigue (Larivière et al, 2004;Yao et al, 2020). Besides muscle pain and hand-arm discomfort, fundamental hand functions like grip strength can be reduced especially after long-term HAV exposure (Gerhardsson & Hagberg, 2019).…”
Section: Introductionmentioning
confidence: 99%